A Meta-analytic Synthesis: Examining the Academic Impacts of Feedback on Student Achievement - Baliram, Nalline S.; Youde, Jeffrey J. (International Dialogues on Education Journal, 2018)
Feedback can be defined by Irons (2008) as “any information, process or activity which affords or accelerates student learning based on comments relating to either formative or summative assessment activities” (p. 7). The current study aims to synthesize quantitative research studies to further explore the impact of feedback on academic achievement. Results indicated the overall summary effect to be moderate and statistically significant (Hedges’ g = .40), thus lending support to the notion that feedback, considered a best practice, positively influences academic achievement. Moderator results suggested that teacher-provided and content-specific feedback at the K-12 level positively impacted student performance in the academic discipline. However, further research is warranted to explore the construct.